DOING REALIST RESEARCH - Emmel, Nick, editor; Greenhalgh, Joanne editor; Manzano, Ana editor; Monaghan, Mark editor; Dalkin, Sonia editor (Thousand Oaks, California : Sage, 2018)
Bringing together leading theorists, researchers and policy makers with expertise in using realist methods, this book is a definitive guide to putting realist methodologies into practice. Not just an overview of the field, this book looks to extend current debates and apply realist methods to new and practical challenges in social research. Featuring practical, worked examples of how to turn theory into evidence, it empowers readers not just to understand realist methods, but to use them. It will help readers: - Negotiate the complexity of relational systems - Understand the importance and relevance of cumulative theory - Address concerns over data sources and quality - Be flexible and creative in realist approaches - Produce useful evidence for policy. Sophisticated and globally minded, this book is the perfect addition to the ongoing development and application of realist methods across evaluation, synthesis, and social research.